The Complete Python and PostgreSQL Developer Course - Salvatierra, Jose; Percival, Rob (Packt Publishing, 2019)
Build 9 projects and master two essential and modern technologies: Python and PostgreSQL About This Video Gain comprehensive understanding of software and programming with Python Create basic beginner-level applications to advanced engaging applications using Python In Detail Ever wanted to learn one of the most popular programming languages on the planet? Why not learn two of the most popular at the same time? Python and SQL are widely used by small to large technology companies thanks to their powerful, yet extremely flexible features. While Python is used in the industry for embedded software, web development, desktop applications, and mobile apps, PostgreSQL allows your applications to become even more powerful by storing, retrieving, and filtering through large datasets easily. This course is your one-stop-shop for everything Python and PostgreSQL. You'll advance from an absolute Python and PostgreSQL beginner to an experienced software developer. Get ready to transform your world and become a super-confident app developer!
Online resource; Title from title screen (viewed July 10, 2019)
Keywords: PostgreSQL; Python (Computer program language); Application software -- Development; Python (Langage de programmation); Logiciels d'application; Développement; Electronic videos